Zazaeil
Zazaeil

Reputation: 4119

`(a -> b) -> (c -> d)` in Haskell?

This is yet another Haskell-through-category-theory question.

Let's take something simple and well-known as an example. fmap? So fmap :: (a -> b) -> f a -> f b, omitting the fact that f is actually a Functor. As far as I understand, (a -> b) -> f a -> f b is nothing but a syntax sugar for the (a -> b) -> (f a -> f b); hence conclusion:

(1) fmap is a function producing a function.

Now, Hask contains functions as well, so (a -> b) and, in particular, (f a -> f b) is an object of the Hask (because objects of the Hask are well-defined Haskell types - a-ka mathematical sets - and there indeed exists set of type (a -> b) for each possible a, right?). So, once again:

(2) (a -> b) is an object of the Hask.

Now weird thing happens: fmap, obviously, is a morphism of the Hask, so it is a function, that takes another function and transform it to a yet another function; final function hasn't been applied yet.

Hence, one needs one more Hask's morphism to get from the (f a -> f b) to the f b. For each item i of type a there exists a morphism apply_i :: (f a -> f b) -> f b defined as \f -> f (lift i), where lift i is a way to build an f a with particular i inside.

The other way to see it is GHC-style: (a -> b) -> f a -> f b. On the contrast with what I've written above, (a -> b) -> f a is mapping to the regular object of the Hask. But such a view contradicts fundamental Haskell's axiom - no multivariate functions, but applied (curried) alternatives.


I'd like to ask at this point: is (a -> b) -> f a -> f b suppose to be an (a -> b) -> (f a -> f b) -> f b, sugared for simplicity, or am I missing something really, really important there?

Upvotes: 6

Views: 1698

Answers (4)

duplode
duplode

Reputation: 34378

For the sake of completeness, this answer focuses on a point that was addressed in various comments, but not by the the other answers.

The other way to see it is GHC-style: (a -> b) -> f a -> f b. On the contrast with what I've written above, (a -> b) -> f a is mapping to the regular object of the Hask.

-> in type signatures is right-associative. That being so, (a -> b) -> f a -> f b is really the same as (a -> b) -> (f a -> f b), and seeing (a -> b) -> f a in it would be a syntactic mix-up. It is no different from how...

(++) :: [a] -> [a] -> [a]

... doesn't mean that partially applying (++) will give us an [a] list (rather, it gives us a function that prepends some list).

From this point of view, the category theory questions you raise (for instance, on "need[ing] one more Hask's morphism to get from the (f a -> f b) to the f b") are a separate matter, addressed well by Jorge Adriano's answer.

Upvotes: 2

Now weird thing happens: fmap, obviously, is a morphism of the Hask, so it is a function, that takes another function and transform it to a yet another function; final function hasn't been applied yet.

Hence, one needs one more Hask's morphism to get from the (f a -> f b) to the f b. For each item i of type a there exists a morphism apply_i :: (f a -> f b) -> f b defined as \f -> f (lift i), where lift i is a way to build an f a with particular i inside.

The notion of application in category theory is modelled in the form of CCC's - Cartesian Closed Categories. A category 𝓒 is a CCC if you have a natural bijection 𝓒(X×Y,Z) ≅ 𝓒(X,Y⇒Z).

In particular this implies that there exists a natural transformation 𝜺 (the evaluation), where 𝜺[Y,Z]:(Y⇒Z)×Y→Z, such that for every g:X×Y→Z there exists a 𝝀g:X→(Y⇒Z) such that, g = 𝝀g×id;𝜺[Y,Z]. So when you say,

Hence, one needs one more Hask's morphism to get from the (f a -> f b) to the f b.

The way you go from (f a -> f b) to the f b, or using the notation above, from (f a ⇒ f b) is via 𝜺[f a,f b]:(f a ⇒ f b) × f a → f b.

The other important point to keep in mind is that in Category Theory "elements" are not primitive concepts. Rather an element is an arrow of the form 𝟏→X,where 𝟏 is the terminal object. If you take X=𝟏 you have that 𝓒(Y,Z) ≅ 𝓒(𝟏×Y,Z) ≅ 𝓒(𝟏,Y⇒Z). That is, the morphisms g:Y→Z are in bijection to elements 𝝀g:𝟏→(Y⇒Z).

In Haskell this means functions are precisely the "elements" of arrow types. So in Haskell an application h y would be modelled via the evaluation of 𝝀h:𝟏→(Y⇒Z) on y:𝟏→Y. That is, the evaluation of (𝝀h)×y:𝟏→(Y⇒Z)×Y, which is given by the composition (𝝀h)×y;𝜺[Y,Z]:𝟏→Z.

Upvotes: 3

chepner
chepner

Reputation: 531165

fmap is actually an entire family of morphisms. A morphism in Hask is always from a concrete type to another concrete type. You can think of a function as a morphism if the function has a concrete argument type and a concrete return type. A function of type Int -> Int represents a morphism (an endomorphism, really) from Int to Int in Hask. fmap, however has type Functor f => (a -> b) -> f a -> f b. Not a concrete type in sight! We just have type variables and a quasi-operator => to deal with.

Consider the following set of concrete function types.

Int -> Int
Char -> Int
Int -> Char
Char -> Char

Further, consider the following type constructors

[]
Maybe

[] applied to Int returns a type we could call List-of-Ints, but we usually just call [Int]. (One of the most confusing things about functors when I started out was that we just don't have separate names to refer to the types that various type constructors produce; the output is just named by the expression that evaluates to it.) Maybe Int returns the type we just call, well, Maybe Int.

Now, we can define a bunch of functions like the following

fmap_int_int_list :: (Int -> Int) -> [Int] -> [Int]
fmap_int_char_list :: (Int -> Char) -> [Int] -> [Char]
fmap_char_int_list :: (Char -> Int) -> [Char] -> [Int]
fmap_char_char_list :: (Char -> Char) -> [Char] -> [Char]
fmap_int_int_maybe :: (Int -> Int) -> Maybe Int -> Maybe Int
fmap_int_char_maybe :: (Int -> Char) -> Maybe Int -> Maybe Char
fmap_char_int_maybe:: (Char -> Int) -> Maybe Char -> Maybe Int
fmap_char_char_maybe :: (Char -> Char) -> Maybe Char -> Maybe Char

Each of these is a distinct morphism in Hask, but when we define them in Haskell, there's a lot of repetition.

fmap_int_int_list f xs = map f xs
fmap_int_char_list f xs = map f xs
fmap_char_int_list f xs = map f xs
fmap_char_char_list f xs = map f xs
fmap_int_int_maybe f x = case x of Nothing -> Nothing; Just y -> Just (f y)
fmap_int_char_maybe f x = case x of Nothing -> Nothing; Just y -> Just (f y)
fmap_char_int_maybe f x = case x of Nothing -> Nothing; Just y -> Just (f y)
fmap_char_char_maybe f x = case x of Nothing -> Nothing; Just y -> Just (f y)

The definitions don't differ when the type of f differs, only when the type of x/xs differs. That means we can define the following polymorphic functions

fmap_a_b_list f xs = map f xs
fmap_a_b_maybe f x = case x of Nothing -> Nothing; Just y -> Just (f y)

each of which represents a set of morphisms in Hask.

fmap itself is an umbrella term we use to refer to constructor-specific morphisms referred to by all the polymorphic functions.

With that out of the way, we can better understand fmap :: Functor f => (a -> b) -> f a -> f b.

Given fmap f, we first look at the type of f. We might find out, for example, that f :: Int -> Int, which means fmap f has to return one of fmap_int_int_list or fmap_int_int_maybe, but we're not sure which yet. So instead, it returns a constrained function of type Functor f => (Int -> Int) -> f Int -> f Int. Once that function is applied to a value of type [Int] or Maybe Int, we'll finally have enough information to know which morphism is actually meant.

Upvotes: 5

leftaroundabout
leftaroundabout

Reputation: 120711

is (a -> b) -> f a -> f b suppose to be an (a -> b) -> (f a -> f b) -> f b, sugared for simplicity

No. I think what you're missing, and it's not really your fault, is that it's only a very special case that the middle arrow in (a -> b) -> (f a -> f b) can be called morphism in the same way as the outer (a -> b) -> (f a -> f b) can. The general case of a Functor class would be (in pseudo-syntax)

class (Category (──>), Category (~>)) => Functor f (──>) (~>) where
  fmap :: (a ──> b) -> f a ~> f b

So, it maps morphisms in the category whose arrows are denoted ──> to morphisms in the category ~>, but this morphism-mapping itself is just plainly a function. Your right, in Hask specifically function-arrows are the same sort of arrows as the morphism arrows, but this is mathematically speaking a rather degenerate scenario.

Upvotes: 6

Related Questions